Audit Firm Mergers and Low Balling - W.J, Liu; Cao, June (2023)
Motivation: This paper investigates whether audit firm mergers affect audit fee discounts in the initial year. The numerous mergers of audit firms in China’s capital market provide a quasi-natural experiment to investigate this issue.